2021
DOI: 10.3390/ani11113181
|View full text |Cite
|
Sign up to set email alerts
|

Feed Intake of Growing Dairy Heifers Raised under Tropical Conditions: A Model Evaluation Using Meta-Analysis

Abstract: Several models for predicting dry matter intake (DMI) of replacement dairy heifers have been developed; however, only a few have been evaluated using data from heifers of different breeds raised under tropical conditions. Thus, the objective of this study was to evaluate the DMI equations for dairy heifers managed under tropical conditions. A total of 230 treatment means from 61 studies using dairy heifers (n = 1513 heifers, average body weight = 246 kg) were used. The animals were grouped into two groups base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…The recent document published by NASEM (2021) also, practically, does not include heifer data from genetic groups other than HOL. However, in recent years, studies on H × G heifers have been published regarding DMI (Oliveira and Ferreira, 2016;Busanello et al, 2021), growth requirements (Castro et al, 2020), and mammary gland development (Albino et al, 2017;Silva et al, 2018). In addition, recent research on HOL cattle can be found in terms of DMI (Hoffman et al, 2008), growth requirements (Albino et al, 2015;Jiao et al, 2015), and body growth (Heinrichs et al, 2017;Silva et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The recent document published by NASEM (2021) also, practically, does not include heifer data from genetic groups other than HOL. However, in recent years, studies on H × G heifers have been published regarding DMI (Oliveira and Ferreira, 2016;Busanello et al, 2021), growth requirements (Castro et al, 2020), and mammary gland development (Albino et al, 2017;Silva et al, 2018). In addition, recent research on HOL cattle can be found in terms of DMI (Hoffman et al, 2008), growth requirements (Albino et al, 2015;Jiao et al, 2015), and body growth (Heinrichs et al, 2017;Silva et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, studies on H×G heifers have been published regarding dry matter intake Busanello et al, 2021), growth requirements , and mammary gland development (Albino et al, 2017;. In addition, recent research on HOL cattle can be found in terms of dry matter intake , growth requirements (Albino et al, 2015;, and body growth (Heinrichs et al, 2017;.…”
Section: Discussionmentioning
confidence: 99%